1989
DOI: 10.1212/wnl.39.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in patients with fusiform vertebrobasilar aneurysms

Abstract: We studied seven patients with brainstem infarction and large fusiform vertebrobasilar (VB) aneurysms to clarify the clinical, radiologic, and pathologic features. All presented with pontine infarcts; one also had a cerebellar infarct. VB TIAs preceded brainstem infarction in four patients. Angiography and CT documented VB fusiform aneurysmal dilatation. Four had intraluminal thrombi and one had severe basilar artery stenosis. Two distinct clinical pictures emerged: unilateral pontine infarcts with favorable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 0 publications
2
70
0
3
Order By: Relevance
“…VFAs most commonly manifest as posterior circulation ischemic strokes, but they may also cause cranial nerve palsies, brainstem compression, obstructive hydrocephalus, and intraparenchymal or subarachnoid hemorrhage (SAH). 5,14,[18][19][20][21][22]29 VFAs have an ominous natural history with a reported mortality up to 30%. 3,24,29 Passero and Rossi reported that 43% of patients without treatment experienced anatomical progression and 60% experienced new symptoms.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…VFAs most commonly manifest as posterior circulation ischemic strokes, but they may also cause cranial nerve palsies, brainstem compression, obstructive hydrocephalus, and intraparenchymal or subarachnoid hemorrhage (SAH). 5,14,[18][19][20][21][22]29 VFAs have an ominous natural history with a reported mortality up to 30%. 3,24,29 Passero and Rossi reported that 43% of patients without treatment experienced anatomical progression and 60% experienced new symptoms.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, pathological changes in the arterial wall, consisting primarily in defects in the internal elastic lamina with thinning of the media secondary to smooth muscle atrophy, 14 -16 may predispose patients to intracranial bleeding of various kinds. Knowledge of hemorrhagic stroke as a clinical feature of VBD has come from case reports involving a small number of patients.…”
mentioning
confidence: 99%
“…The last two terms seem to designate different degrees of progression of the same disease. Etiopathogenic heterogeneity is suggested by descriptions of a number of wall abnormalities 1,[6][7][8][9][10][11] . The most frequent findings in affected arteries have been loss of medial layer components, collagen fiber degeneration, fibrosis, atherosclerotic changes and parietal thrombosis 7,8,10,11 .…”
mentioning
confidence: 99%
“…FAs may be asymptomatic or cause brain stem and cranial nerve compression, subarachnoid hemorrhage (SAH) or infarction. The latter is more commonly caused by thrombosis of small collateral branches or embolism to distal arteries 3,9 . Complete occlusion of the affected vessel appears to be rare 12 .…”
mentioning
confidence: 99%